2003
DOI: 10.1007/s00244-002-0131-9
|View full text |Cite
|
Sign up to set email alerts
|

Global Pollution Monitoring of PCBs and Organochlorine Pesticides Using Skipjack Tuna as a Bioindicator

Abstract: Concentrations of organochlorines (OCs) representing persistent organic pollutants (POPs), such as polychlorinated biphenyls (PCBs), dichlorodiphenyl trichloroethane and its metabolites (DDTs), chlordane compounds (CHLs), hexachlorocyclohexane isomers (HCHs), and hexachlorobenzene (HCB), were determined in the liver of skipjack tuna (Katsuwonus pelamis) collected from the offshore waters of various regions in the world (offshore waters around Japan, Taiwan, Philippines, Indonesia, Seychelles, and Brazil, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(44 citation statements)
references
References 36 publications
8
35
0
1
Order By: Relevance
“…In previous research on epipelagic foraging marine predators from the North Pacific Ocean, intraspecific variability in POP concentrations was observed in shearwaters (Calonectris leucomelas) (Ito et al, 2013), skipjack tuna (Katsuwonus pelamis) (Ueno et al, 2003), humpback whales (Elfes et al, 2010), and Hawaiian monk seals (Lopez et al, 2012), and attributed to differences in geographic location. However, the influence of foraging behavior on POP concentrations may depend on foraging characteristics beyond geography.…”
Section: Discussionmentioning
confidence: 96%
“…In previous research on epipelagic foraging marine predators from the North Pacific Ocean, intraspecific variability in POP concentrations was observed in shearwaters (Calonectris leucomelas) (Ito et al, 2013), skipjack tuna (Katsuwonus pelamis) (Ueno et al, 2003), humpback whales (Elfes et al, 2010), and Hawaiian monk seals (Lopez et al, 2012), and attributed to differences in geographic location. However, the influence of foraging behavior on POP concentrations may depend on foraging characteristics beyond geography.…”
Section: Discussionmentioning
confidence: 96%
“…Chlordane was one type of the OCPs that occurred most frequently in the environment all over the world, however, only limited literatures reported the concentration levels of chlordane in the open ocean water (Iwata et al, 1993). Recently, some researchers suggested that skipjack tuna is a suitable bioindicator for monitoring the global distribution of organochlorines in offshore waters and the open ocean (Ueno et al, 2003). Chlordane levels were found to be the second highest OCPs in skipjack tuna liver, which may imply that significant amounts of chlordane exist in seawater.…”
Section: Concentrations In Watermentioning
confidence: 99%
“…In recent years, the production of OCPs was either eliminated or their release into the environment reduced under the Stockholm Convention on OCPs, which was adopted by many countries. However, in Southeast Asian countries, the late production ban as well as the current legal and illegal application for agricultural practices and for the control of certain diseases, such as malaria, typhus and cholera, have contributed to higher concentrations of OCPs in the environment (i.e., the atmosphere, water and sediment) (Hung and Thiemann, 2002;Iwata et al, 1994;Zhang et al, 2002), aquatic wildlife (e.g., mussels) (Ueno et al, 2003) and the human population (e.g., human breast milk) (UNEP, 2002;Wong et al, 2002). Oceanic waters are a receptor of land based pollutant sources, and coastal waters are particularly affected by inputs of OCPs via discharges of sewage, industrial effluents and significant rivers that drain into the marginal seas of China.…”
Section: Introductionmentioning
confidence: 99%
“…These levels are lower than those around most parts of Japan. A huge amount of PCB was manufactured in Japan [28], so relatively high PCB levels were observed in Japanese coastal samples compared with other Asian countries [3,[10][11][12]. The mean concentrations of CHLs and HCHs were also lower in offshore Korean waters than in other Asian locations.…”
Section: Discussionmentioning
confidence: 72%
“…Globally, research on the distribution and accumulation characteristics of POPs in the open ocean has utilized various marine organisms, including cephalopods, fish and mammals as monitoring species [7][8][9][10][11][12][13][14]. In particular, cephalopods are easy to collect and reflect the concentrations of compounds in ambient seawater promptly because they breathe through gills [15].…”
Section: Introductionmentioning
confidence: 99%